Causal Effects of Genetically Predicted Iron Status on Sepsis: A Two-Sample Bidirectional Mendelian Randomization Study - Hu, Yuanlong; Cheng, Xiaomeng; Mao, Huaiyu; Chen, Xianhai; Cui, Yue; Qiu, Zhanjun (Frontiers in Nutrition, 2021)
Background/Aim: Several observational studies showed a significant association between elevated iron status biomarkers levels and sepsis with unclear direction of causality. A two-sample bidirectional mendelian randomization (MR) study was designed to identify the causal direction between four iron status traits and sepsis. Methods: Seven iron status traits were studied, including serum iron, ferritin, transferrin saturation, transferrin, hemoglobin, erythrocyte count and reticulocyte count. MR analysis was first performed to estimate the causal effect of iron status on the risk of sepsis, and then performed in the opposite direction. The multiplicative random-effects and fixed-effects inverse-variance weighted, weighted median-based method and MR-Egger were applied. MR–Egger regression, MR pleiotropy residual sum and outlier and Cochran’s Q statistic methods were used to assess heterogeneity and pleiotropy. Results: Genetically predicted high levels of serum iron (OR = 1.21, 95%CI = 1.13 to 1.29, p = 3.16×10-4), ferritin (OR = 1.32, 95%CI = 1.07 to 1.62, p = 0.009) and transferrin saturation (OR = 1.14, 95%CI = 1.06 to 1.23, p = 5.43×10-4) were associated with an increased risk of sepsis. No significant causal relationships between sepsis and other four iron status biomarkers were observed. Conclusions: This present bidirectional MR analysis suggests the causal association of the high iron status with sepsis susceptibility, while the reverse causality hypothesis did not hold. The levels of transferrin, hemoglobin, erythrocytes and reticulocytes were not significantly associated with sepsis. Further studies will be required to confirm the potential clinical value of such a prevention and treatment strategy.